Prenatal ultrasound findings and clinical outcomes of uniparental disomy: a retrospective study - Cui-Yi Wu; Yi Zhou; Xia Yin; Ruan Peng; Hong-Ning Xie (BMC, 2024)
Abstract Background Uniparental disomy is the inheritance of a homologous chromosome pair or part of homologous chromosomes from only one parent. However, the clinical significance of uniparental disomy and the difference among the prognosis of involvement of different chromosomes remain unclear. Objective To assess the associated prenatal ultrasound presentations and clinical outcomes of uniparental disomy on different chromosomes and to analyze the relationship between prenatal ultrasound markers and clinical outcomes. Study design We retrospectively analyzed data from fetuses with uniparental disomy diagnosed using chromosome microarray analysis with the Affymetrix CytoScan HD array at our institution between January 2013 and September 2022. The relationship between prenatal ultrasound findings, the involved chromosome(s), and clinical outcomes was evaluated. Results During the study period, 36 fetuses with uniparental disomy were diagnosed, and two cases were excluded for non-available postnatal data. Finally, 34 fetuses were included in our study, of which 30 (88.2%) had uniparental disomy occurring on a single chromosome, while four (11.8%) were identified with uniparental disomy on different chromosomes. The most frequently involved chromosomes were chromosomes 16, X and 2, which presented in 8 (23.5%), 5 (14.7%) and 4 (11.8%), respectively. Prenatal ultrasound abnormalities were detected in 21 fetuses, with the most common category being multiple abnormalities (12 (57.1%)). Fetal growth restriction was identified in 14 (41.2%) fetuses, all of which coexisted with other abnormal findings. The rate of adverse perinatal outcomes in patients with uniparental disomy and fetal abnormalities was significantly higher than those without abnormalities (76.2% versus 15.4%, P = 0.002). The incidence of fetal or neonatal death was significantly higher in fetuses with fetal growth restriction than those without (85.7% versus 30.0%, P = 0.004). Conclusions The prognosis of fetuses with uniparental disomy combined with fetal abnormalities, especially fetal growth restriction, was much poorer than those without.